Durability Indicators for Sustainable Self-Consolidating High-Strength Concrete Incorporating Palm Oil Fuel Ash - Salam, Mohammed Abdus; Safiuddin, Md.; Jumaat, Mohd Zamin (MDPI, 2018)
This paper presents the durability indicators for sustainable self-consolidating high-strength concrete (SCHSC) including palm oil fuel ash (POFA) as a supplementary cementing material (SCM). SCHSC mixes were prepared by varying the water to binder (W/B) ratio and POFA content. The W/B ratio was varied in the range of 0.25 to 0.40, and the POFA content differed in the range of 10-30% to produce the desired SCHSC mixes. The tests conducted on the freshly mixed SCHSCs to evaluate their filling ability, passing ability, and segregation resistance were slump flow, J-ring flow, and sieve segregation, respectively. To evaluate the durability of the hardened SCHSCs, the compressive strength, water absorption, and permeable porosity were examined along with the ultrasonic pulse velocity (UPV). The correlations between different hardened properties were derived to ascertain the durability indicators for sustainable SCHSCs. It was observed that most of the SCHSCs possessed excellent filling ability and passing ability with adequate segregation resistance. The test results also revealed that the compressive strength and UPV increased, whereas the water absorption and permeable porosity decreased with a lower W/B ratio and a higher amount of POFA (up to 20% weight content). Moreover, strong correlations were found between the different hardened properties of SCHSC. These correlations were used to determine the durability indicators for sustainable SCHSC with respect to compressive strength, permeable porosity, and water absorption. In accordance with the derived durability indicators, the sustainable SCHSC mixes produced in this study had the durability levels varying from "high" to "outstanding".